House Dust Mite Allergen Levels of Der p1 and Der f1 in Houses of Asthmatic Children - Abbas Dabbaghzadeh; Javad Ghaffari; Mohammad Feridoni; Afrooz Alipour (Mazandaran University of Medical Sciences, 2020)
Background: Exposure to house dust mites is an important cause of asthma among children. The main asthma-causing mites found in homes are Dermatophagoides farinae and Dermatophagoides. pteronyssinus. Der f1 or Der p1 are allergens of the mentioned mites. This study aimed to assess the levels of Der p1, and Der f1 in the homes of families that had a case of childhood asthma in a northern city of Iran and to determine the association between indoor house environment and the level of mites allergens present there.  Objectives: This study aimed to evaluate House Dust Mite Allergen Levels of Der p1 and Der f1 in Houses of Asthmatic Children.  Methods: Dust samples were collected from bedrooms of 91 homes of families that had cases of childhood asthma. Families filled a questionnaire about demographical characteristics and the indoor condition of their living environment. The levels of Der f1 and Der p1 were measured by enzyme-linked immunosorbent assay (ELISA). Statistical analysis was performed in SPSS v. 24 and a P-value less than 0.05 was considered significant. Results: we found that Der p1 was more prevalent than Der f1 among samples. The mean concentration of Der p1 concentration was 271.35 ng/g (9 times greater than the concentration of Der f1). When the indoor environment status was evaluated, it was found that keeping pets and having old carpets are associated with Der f1 (P<0.05). However, no significant association was found between Der p1 and the indoor conditions of the home. Conclusions: Our study showed that Der p1 level is higher than Der f1 level in the houses of children with asthma. We suggest removing carpets and pets from the house.